2013
DOI: 10.1186/1743-0003-10-100
|View full text |Cite
|
Sign up to set email alerts
|

Augmented visual feedback counteracts the effects of surface muscular functional electrical stimulation on physiological tremor

Abstract: BackgroundRecent studies suggest that surface muscular functional electrical stimulation (FES) might suppress neurological upper limb tremor. We assessed its effects on upper limb physiological tremor, which is mainly driven by mechanical-reflex oscillations. We investigated the interaction between FES and augmented visual feedback, since (a) most daily activities are performed using visual cues, and (b) augmented visual feedback exacerbates upper limb tremor.Methods10 healthy subjects (23.4 ± 7.7 years) perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Further, respiratory motion is semi periodic in nature with slow-varying characteristics (frequency range < 1 Hz). Physiological tremor is a quasi periodic signal and lies in the high frequency range (6)(7)(8)(9)(10)(11)(12)(13)(14). Together with the nonstationary characteristics, the multistep prediction becomes much more challenging with LS-SVM compared to the other physiological motions like respiratory motions.…”
Section: B Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Further, respiratory motion is semi periodic in nature with slow-varying characteristics (frequency range < 1 Hz). Physiological tremor is a quasi periodic signal and lies in the high frequency range (6)(7)(8)(9)(10)(11)(12)(13)(14). Together with the nonstationary characteristics, the multistep prediction becomes much more challenging with LS-SVM compared to the other physiological motions like respiratory motions.…”
Section: B Methodsmentioning
confidence: 98%
“…It has multiple dominant frequencies usually distributed between 6 to 14 Hz with an amplitude of 50 to 100 μm in each principal axis [1]- [4]. The dominant frequencies of physiological tremor are usually limited to 4 Hz bandwidth (for e.g., [8][9][10][11][12] Hz for a typical healthy subject) [4]- [8]. The analysis conducted on physiological tremor time series in [4]- [6] and [9]- [12] suggested that tremor is nonstationary in nature and exhibits significant variations in amplitude, frequency, and bandwidth over the time.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were comfortably seated in an armchair, and equipped with 2 triaxial accelerometers, located at the right index finger and at the right metacarpal region (see Grimaldi et al, 2013 ). They were asked to maintain the upper limbs motionless horizontally in front of them and parallel to the floor.…”
Section: Methodsmentioning
confidence: 99%
“…The 30-s time series were segmented into 10 segments of 3 s. Auto-spectra of 10 sequential 3 s data epochs were averaged to produce smoothed auto-spectra, with mean removal and a Hamming window for each data segment ( 17 ). The following spectral parameters were extracted, and means were computed for the three experimental conditions: maximal PSD, peak frequency of power spectra, center frequency (median value of the area below the power spectrum), and frequency dispersion (frequency width of the interval around the center frequency that contains 66% of the total power spectrum) ( 19 , 20 ). Composite data (square root of the sum of the accelerations squared for all three axes) were processed as reported earlier ( 20 , 21 ).…”
Section: Transcranial Cerebello-cerebral Direct Current Stimulation (mentioning
confidence: 99%
“…The following spectral parameters were extracted, and means were computed for the three experimental conditions: maximal PSD, peak frequency of power spectra, center frequency (median value of the area below the power spectrum), and frequency dispersion (frequency width of the interval around the center frequency that contains 66% of the total power spectrum) ( 19 , 20 ). Composite data (square root of the sum of the accelerations squared for all three axes) were processed as reported earlier ( 20 , 21 ). Data presented in Section “ Results ” are mean ± SD of the three recordings performed in each experimental condition.…”
Section: Transcranial Cerebello-cerebral Direct Current Stimulation (mentioning
confidence: 99%